Tempered Sympathy: Canada’s Reaction to the Independence Movement in Algeria, 1954-1962 - Gendron, Robin (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1998)
AbstractThis article examines the reaction of the Canadian government to the Algerian war for independence from France from 1954 to 1962. It reveals that, while sympathetic to the ambitions of colonial peoples to determine their own national destinies, the Canadian government often judged colonial issues after the Second World War by the impact they had on the North Atlantic Treaty Organisation, Canadian security interests and the Cold War. Given that the Algerian war threatened France's ability and willingness to contribute to NATO during this period the Canadian government felt compelled to support France's efforts to retain its North African colony both politically and militarily. Canadian officials wanted France's participation in NATO and were unwilling to antagonise France by opposing its Algerian policies. In this instance national security interests were of a higher priority for the Canadian government than support for the principle of national self-determination for colonial peoples.